Comparison of polarization and polarimetric optical tomography methods for recognition of tissue simulators inside breast phantom - Miernicki, Sławomir; Sobotka, Piotr Kamil; Domański, Andrzej Witold (Photonics Letters of Poland, 2011)
In the paper we present results of recognition of tissues simulators inside breast phantom based on polarization analysis of scattered light as well as polarimetric optical tomography method based on Mueller Stokes formalism. Blood, fat and muscle tissues were simulated by 10mm diameter probes with red dye, 20% Intralipid™ and water with polarizing foil respectively. All tissue simulators were placed inside container (diameter 120mm) filled by 0.1% solution of Intralipid™. Different kind of polarization state of laser beam (670nm, 35 mW) was used for lighting the container (breast phantom). Results of measurement show that polarization optical tomography easier allows to recognize different kind of tissue simulators. On the other hand polarimetric optical tomography allows for better recognition of angular placement of tissue simulators. Full Text: PDF References: Huang, D. E., Swanson, A. C., Lin, P., Schuman, J. S., Stinson, W. G., Chang, W. M., Hee, R., Flotte, Gregory, T. K., Puliafito, C. A. and Fujimoto, J. G., „Optical coherent tomography”, Science 254, (1991) [CrossRef] Fercher, A. F., Drexler, W., Hitzenberger, C. K. and Lasser, T., „Optical coherence tomography—principles and applications”, Rep. Prog. Phys. 66, (2003) [CrossRef] Bajraszewski, T., Gorczyńska, I., Szkulmowska, A., Szkulmowski, M., Targowski P. and Kowalczyk, A. „Spectral Optical Coherence Tomography in ophthalmology”, Proceedings of SPIE 5959, (2005) [CrossRef] Hielscher, A. H., Klose, A. D. and Hanson, K. M., „Gradient-Based Iterative Image Reconstruction Scheme for Time-Resolved Optical Tomography, IEEE Transactions on Medical Imaging”, Vol. 18, No. 3, (1999) [CrossRef] Tarvainen, T., Vauhkonen, M., Kolehmainen,V., Kaipio, J. P. and Arridge S. R., „Utilizing the Radiative Transfer Equation in Optical Tomography”, PIERS Online, Vol. 4, No. 6, (2008) [CrossRef] Nielsen, T., Brendel, B., Ziegler, R., Beek, M., Uhlemann, F., Bontus, C. and Koehler, T., „Linear image reconstruction for a diffuse optical mammography system in a noncompressed geometry using scattering fluid”, Applied Optics, Vol. 48, No. 10, (2009) [CrossRef] Domanski, A. W., Rytel, M. and Wolinski, T. R., „Polarization optical tomography based on analysis of Mueller matrix elements of scattered light”, Proceedings of SPIE Vol. 5959, (2005) [CrossRef] Michels R., Foschum F, and Kienle A., „Optical properties of fat emulsions” OPTICS EXPRESS 5908, Vol. 16, No. 8, (2008) [CrossRef] G. Yao, L.V. Wang, „Two-dimensional depth-resolved Mueller matrix characterization of biological tissue by optical coherence tomography”, Optics Letters, vol. 24, no. 8, (1999). [CrossRef]